2020
DOI: 10.1017/lap.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Who Shot the Bullets? Exposure to Violence and Attitudes Toward Peace: Evidence from the 2016 Colombian Referendum

Abstract: Does exposure to violence affect attitudes toward peace? Civilians living in war zones see peace agreements as an opportunity to improve their security prospects. However, in multiparty conflicts, this does not automatically translate into support for peace. Support hinges on the interplay between which faction has victimized civilians in the past and which faction is sitting at the negotiation table. If civilians have been victimized by the group that is involved in the peace agreement, they will be likely to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 65 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…More generally, our findings contribute to the emerging research agenda on perceptions of peace agreements (e.g., Tellez 2019;Matanock and Garbiras-Díaz 2018;Kreiman and Masullo 2020), adding a long-term perspective. In so doing, this study draws on and adds support to studies that have shown that wartime cleavages may have long-term implications for political preferences in the post-war era (e.g., Balcells 2012).…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…More generally, our findings contribute to the emerging research agenda on perceptions of peace agreements (e.g., Tellez 2019;Matanock and Garbiras-Díaz 2018;Kreiman and Masullo 2020), adding a long-term perspective. In so doing, this study draws on and adds support to studies that have shown that wartime cleavages may have long-term implications for political preferences in the post-war era (e.g., Balcells 2012).…”
Section: Discussionsupporting
confidence: 66%
“…As we suggest above, when the memory of the armed conflict becomes more distant and the fear of renewed violence diminishes, people’s assessments of the peace agreement may be more based on principles and moral judgements, and less based on fear and safety-seeking (c.f. Tellez 2019; Kreiman and Masullo 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations